Gender differences in psychosomatic complaints across occupations and time from 2006 to 2018 in Germany: a repeated cross-sectional study - Julia Grasshoff; Batoul Safieddine; Stefanie Sperlich; Johannes Beller (BMC Public Health)
Abstract Background Previous research indicates that women report more psychosomatic complaints at work compared to men. However, there is a lack of research examining this gender gap across different occupational subgroups and over time. Methods The study utilized data from the nationwide German Employment Survey of the Working Population on Qualification and Working Conditions conducted in 2005/2006, 2011/2012, and 2017/ 2018. First, gender differences in psychosomatic complaints were analysed within the occupational subgroups categorized as white-collar high-skilled, white-collar low-skilled, blue-collar high-skilled and blue-collar low-skilled workers. Second, gender stratified time trends of psychosomatic complaints were analysed. A total of 58,759 participants were included in the analysis. Results Women consistently reported significantly higher levels of psychosomatic complaints compared to men across all years examined. The largest differences were observed in white-collar high-skilled occupations. From 2005/2006 to 2011/2012, gender differences increased; from 2011/2012 to 2017/2018, they stagnated. Conclusions The study revealed that women experience more psychosomatic distress at work than men in all occupational subgroups and time points. White-collar high-skilled workers showed the highest gender gap in psychosomatic complaints. The gender gap widened from 2005/2006 to 2011/2012 and remained stable from 2011/2012 to 2017/2018. Future research should investigate the reasons and implications of this phenomenon, especially considering the increasing proportion of high-skilled white-collar workers, where the gender gap is most evident.